Scutellarin promotes microglia-mediated astrogliosis coupled with improved behavioral function in cerebral ischemia. (July 2016) - Fang, Ming; Yuan, Yun; Lu, Jia; Li, Hong E.; Zhao, Min; Ling, Eng-Ang; Wu, Chun-Yun
Abstract: Scutellarin, an anti-inflammatory agent, has been reported to suppress microglia activation. It promotes astrocytic reaction but through activated microglia. Here we sought to determine more specifically the outcomes of scutellarin treatment in reactive astrocytes in rats subjected to middle cerebral artery occlusion (MCAO). GFAP, MAP-2 and PSD-95 expression was assessed in reactive astrocytes in scutellarin injected MCAO rats. Expression of BDNF, NT-3 and IGF-1, and cell cycle markers cyclin-D1/B1 was also evaluated. In vitro, the above-mentioned proteins were also investigated in TNC 1 and primary astrocytes, treated respectively with conditioned medium from BV-2 microglia with or without pretreatment of scutellarin and lipopolysaccharide. Behavioral study was conducted to ascertain if scutellarin would improve the neurological functions of MCAO rats. In MCAO, reactive astrocytes in the penumbral areas were hypertrophic bearing long extending processes; expression of all the above-mentioned markers was markedly augmented. When compared to the controls, TNC1/primary astrocytes responded vigorously to conditioned medium derived from BV-2 microglia treated with scutellarin + lipopolysaccharide as shown by enhanced expression of all the above markers by Western and immunofluorescence analysis. By electron microscopy, hypertrophic TNC1 astrocytes in this group showed abundant microfilaments admixed with microtubules. In MCAO rats given scutellarin treatment, neurological scores were significantly improved coupled with a marked decrease in infarct size when compared with the matching controls. It is concluded that scutellarin is neuroprotective and that it can amplify astrogliosis but through activated microglia. Scutellarin facilitates tissue remodeling in MCAO that maybe linked to improvement of neurological functions. Highlights: Scutellarin amplified expression of neurotrophic proteins in reactive astrocytes. Scutellarin increased expression of proliferation proteins in reactive astrocytes. Scutellarin improved neurological functions of MCAO rats.